“There’s Nothing Like a Cup of Tea in the Woods”: Continuity, Community and Cultural Validation in Rural Newfoundland Boil-ups - O’Brien, Andrea (Ethnologies, 1999)
This paper presents the Newfoundland boil-up as an integral means of transmitting folk knowledge over time, space and gender boundaries. Boil-ups allow community members to formulate cognitive mapping Systems of the conceptual limits of home through work and leisure activities. In the face of rapid economic change brought about by the closure of the cod fishery, as well as encroachments into rural areas by government and other external agencies, boil-ups have become important as an expression of rural Newfoundland’s distinct culture and society.